The Reduction of Methane Production in the In Vitro Ruminal Fermentation of Different Substrates is Linked with the Chemical Composition of the Essential Oil - Garcia, Florencia; Colombatto, Darío; Brunetti, Maria Alejandra; Martinez, Maria Jose; Moreno, Maria Valeria; Scorcione Turcato, Maria Carolina; Lucini, Enrique Iván; Frossasco, Georgina; Martinez Ferrer, Jorge (MDPI, 2024)
There is interest in identifying natural products capable of manipulating rumen microbial activity to develop new feed additives for ruminant nutrition as a strategy to reduce methane. Two trials were performed using the in vitro gas production technique to evaluate the interaction of substrate (n = 5) and additive (n = 6, increasing doses: 0, 0.3, 3, 30, and 300 µL/L of essential oils—EO—of Lippia turbinata or Tagetes minuta, and monensin at 1.87 mg/L). The two EO utilized were selected because they differ markedly in their chemical composition, especially in the proportion of oxygenated compounds. For both EO, the interaction between the substrate and additive was significant for all variables; however, the interaction behaved differently for the two EO. Within each substrate, the response was dose-dependent, without effects at a low level of EO and a negative outcome at the highest dose. The intermediate dose (30 µL/L) inhibited methane with a slight reduction on substrate digestibility, with L. turbinata being more effective than T. minuta. It is concluded that the effectiveness of the EO to reduce methane production depends on interactions between the substrate that is fermented and the additive dose that generates different characteristics within the incubation medium (e.g., pH); and thus, the chemical nature of the compounds of the EO modulates the magnitude of this response.